Discretion of Morality (Pancasila Moral Relations in The Laws of Political Determination) - Muhammad Azis Zaelani; I Gusti Ayu Ketut Rachmi Handayani; Isharyanto Isharyanto (Alliance of Health Activists (AloHA), 2020)
This study has purpose to determine the form of Pancasila moral relations as the legal ideology of Indonesia in guarding discretion amid political determination. In this study, the conceptual approach was used as a basis for thinking to guide answe tor the problem which then analyzed using qualitative approach. The results showed that Pancasila as the ideology of Indonesian law is able to guard discretion in the form of moral relations that are reflected in discretion users. The implication, it is necessary to optimize the interpretation of the Pancasila in Law Number 30 of 2014 concerning Government Administration to realize the ideals of justice in the bureaucracy as per the Pancasila insight. Therefore, Pancasila morals can guard the use of discretion in political determination. Keywords: Pancasila; discretion; moral